COST OF CULTIVATION AND RESOURCE USE EFFICIENCY OF GROUNDNUT SEED PRODUCTION IN TELANGANA STATE - D. SRINIVASA CHARY, PANNALA DIVAKAR REDDY , SEEMA, R. VIJAYA KUMARI, M. SREENIVASULU and (The Journal of Research, PJTSAU, 2020)
It is well established universally that seed is the basic and most critical input for sustainable agriculture. Quality seed is the pivotal input for sustained growth of agricultural sector and other inputs are contingent upon quality of seed for being optimally effective. Adequate quantity of quality planting material at appropriate time and affordable cost is the objective of the policy makers in order to bring radical changes in agricultural scenario of our country.